2017
DOI: 10.1634/theoncologist.2017-0474
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial Using a Combination of Oxaliplatin, Capecitabine, and Celecoxib with Concurrent Radiation for Newly Diagnosed Resectable Rectal Cancer

Abstract: Lessons Learned. Colorectal cancers exhibit a high level of cyclooxygenase‐2 (COX‐2) expression with strong preclinical rationale for improved clinical outcomes with COX‐2 inhibition. Celecoxib is a COX‐2 inhibitor and we have shown that it can be safely combined with capecitabine and oxaliplatin as part of neoadjuvant treatment with radiation therapy (RT) in rectal cancer.There was a significant improvement in skin toxicity with this combination as compared with historical data. Considering the field has move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…Studies have suggested that the COX-inhibitor was a promising radiosensitizer, which could synergize with radiotherapy in the anti-tumor field (17,30,31,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that the COX-inhibitor was a promising radiosensitizer, which could synergize with radiotherapy in the anti-tumor field (17,30,31,34).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 12 included studies, 5 studies were RCTs (26-30), whereas the other 7 UCTs were conducted using single-arm design (31)(32)(33)(34)(35)(36)(37). Every participant was diagnosed with advanced unresectable or resectable CSC tumors.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…The prognosis for metastatic CRC has significantly improved in the past 10–15 years, with more effective surgical approaches and efficacious chemotherapy regimens making it possible for patients to undergo surgical resection [ 3 ]. Even though the vast majority of metastatic CRC patients (80%–90%) present with unresectable disease, modern combination chemotherapy results in a median survival duration of roughly 20 months [ 4 6 ]. However, evaluating the prognosis of patients with CRC liver metastasis (CRLM) is still challenging, and the results will influence treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of such level of evidence, the management of gastrointestinal tumor has evolved into a multidisciplinary effort that requires chemotherapy, radiation, and surgical oncologists to elucidate a sound clinical treatment plan [18]. In order to reduce the probability of recurrence and to improve overall survival, preoperative chemoradiation and then radical excision is currently the standard of care for locally advanced stages of rectal cancer [19, 20].…”
Section: Discussionmentioning
confidence: 99%